RELATIVE INDEX OF SUSCEPTIBILITY TO THE MAIZE WEEVIL, Sitophilus zeamais, AMONG SOME QPM CORN LINES - SANTOS, JAMILTON P.; GUIMARAES, PAULO E. O.; WAQUIL, JOSÉ M.; FOSTER, JOHN E. (REVISTA BRASILEIRA DE MILHO E SORGO, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:3.0cm 3.0cm 73.7pt 3.0cm; mso-header-margin:2.0cm; mso-footer-margin:36.0pt; mso-gutter-margin:5.65pt; mso-paper-source:15 0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The maize weevil, Sitophilus zeamais, is one important pest of stored corn grain. It is difficult to control and causes large weight and nutritional losses to the grains. The discovery of the gene Opaque-2 (O-2) that enhances the protein quality with Lysine and Tryptophane opened new perspectives to use corn to feed monogastric animals and for human nutrition. However, the soft and farinaceous consistency of the endosperm in the O-2 gene corn increased the susceptibility to maize weevil. To solve this problem the O-2 gene was transferred to normal corn. This new corn was called Quality Protein Maize (QPM). The objective of this study was to evaluate a selected group of corn genotypes for genetic resistance to maize weevil. A parameter named Index of Susceptibility (IS), which considers the progeny number in the F1 generation and the time the insects take to mature from egg to adult was used to measure the susceptibility. Some genotypes had an IS close to resistant control (such as the Cateto-SL, a very hard flint endosperm grain), but some had an IS like the susceptible control. This is an evidence of genetic variability within the QPM genotypes for resistance to maize weevil. It is reported the discovery of a group of experimental QPM hybrids and lines that carry genes for resistance to maize weevil. Also, it is possible to say that the QPM is not necessarily more susceptible to maize weevil damage than it is the normal endosperm type of the commercial corn available on the market.